Early complications after laparoscopic resection of choledochal cyst - Zhang, Bing (Pediatr Surg Int, 2019)
PURPOSE: To investigate the causes and treatments of early complications involving laparoscopic radical resection of choledochal cyst and summarize the experience. METHODS: Children with choledochal cyst treated by laparoscopy in the Department of Pediatric Surgery, Fujian Provincial Maternity and Children’s Hospital, and Guangzhou Women and Children’s Medical Centre, from March 2016 to May 2018, were retrospectively analysed. Demographics, causes and treatments of early complications, liver function analysis and ultrasonography were collected. RESULTS: In total, 231 cases were included; 204 were Type I (156 Type Ia and 46 Type Ic) and 27 were Type IV. No mortality was observed, and 224 cases were successfully laparoscopically operated, while 7 cases were converted to open surgery. Fifteen cases of postoperative developed biliary fistula. There were jejunal Roux loop obstruction in 2 cases and multiple intussusception, anastomotic stenosis after hepaticojejunostomy, residual of choledochal cyst and pancreatic fistula in one each. Patients were followed up ranging from 4 months to 48 months (12.6 ± 0.3 months on average). Postoperative ALT, AST, GGT, TBIL and DBIL all returned to normal during this time. Ultrasonography indicated 5 cases of widened Glisson’s sheath and 1 case of intrahepatic hyperdense shadow. CONCLUSION: Early complications of laparoscopic radical resection of choledochal cyst can be minimized by properly managing preoperative indications and contraindications, carefully interpreting the magnetic resonance cholangiopancreatography results and accumulating experience by the surgeons.